Association between night shift work and cardiovascular disease: a systematic review and dose-response meta-analysis - Xi, Jiayu; Ma, Wenlian; Tao, Yanmin; Zhang, Xiameng; Liu, Linfeng; Wang, Hongyan (Frontiers in Public Health, 2025)
BackgroundShift work, particularly night shift work, has become increasingly prevalent on a global scale and is associated with multiple health issues including type 2 diabetes and cardiovascular diseases (CVD). This study aimed to assess the relationship between night shift work and the incidence and mortality of CVD.MethodSix electronic databases including PubMed, Embase, Cochrane Library, Web of Science, CINAHL, and Scopus were searched from inception until August 10, 2025. Cohort studies eligible for inclusion addressed the association between night shift work and outcomes of CVD. STATA 18.0 software was used for meta-analysis. The dose-response relationship was estimated using generalized least squares regression, and restricted cubic splines were used to analyze potential linear or nonlinear associations. The Newcastle-Ottawa Scale (NOS) was used to assess the quality of the studies. Quality assessment and data extraction were performed independently by two researchers.ResultsTwenty-three cohort studies were included. Overall, this meta-analysis revealed that night shift work significantly increased the risk of total CVD events (RR = 1.13, 95% CI = 1.10–1.16) and total CVD mortality (RR = 1.27, 95%CI = 1.18–1.36). Dose-response analysis indicated that each 5-year increment in shift work duration was associated with a 7% higher risk of CVD incidence (RR = 1.07, 95% CI: 1.04–1.09) and a 4% increased risk of CVD mortality (RR = 1.05, 95% CI: 1.03–1.06). Subgroup analyses identified elevated risks for incident coronary heart disease (CHD) (RR = 1.22, 95% CI = 1.16–1.28) and ischemic heart disease (IHD) (RR = 1.09, 95% CI = 1.05–1.14), but not stroke (RR = 1.06, 95% CI = 0.95–1.18), and night shift work was associated with an increased risk of mortality due to CHD (RR = 1.22, 95% CI = 1.10–1.36), IHD (RR = 1.39, 95% CI = 1.06–1.84), and stroke (RR = 1.49, 95% CI = 1.04–2.12).ConclusionThese findings indicate that night shift work is significantly associated with increased CVD incidence and mortality risk, highlighting the need for targeted prevention strategies.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251060086. CRD: 420251060086.